227k views
1 vote
Find the inverse of the following function. Then prove they are inverses of one another.

f (x)= root 2x-1.

1 Answer

4 votes

Answer:
(x^2+1)/(2)

Explanation:

Given


f(x)=√(2x-1)

We can write it as


\Rightarrow y=√(2x-1)

Express x in terms of y


\Rightarrow y^2=2x-1\\\\\Rightarrow x=(y^2+1)/(2)

Replace y be x to get the inverse


\Rightarrow f^(-1)(x)=(x^2+1)/(2)

To prove, it is inverse of f(x).
f(f^(-1)(x))=x


\Rightarrow f(f^(-1)(x))=\sqrt{2* (x^2+1)/(2)-1}\\\\\Rightarrow f(f^(-1)(x))=√(x^2+1-1)\\\\\Rightarrow f(f^(-1)(x))=x

So, they are inverse of each other.

User Hielsnoppe
by
4.4k points